The Nature of Bradykinesia in Schizophrenia Treated with Antipsychotics - Caligiuri, Michael P. (Psychiatry Res, 2019)
Recognizing drug-induced parkinsonian bradykinesia in psychosis patients can be challenging due to overlapping presentation with psychomotor slowing associated with depression, negative symptoms, or cognitive disturbances. In this study, we apply prior findings on the pathophysiology of bradykinesia in Parkinson’s disease to gain an understanding of motor slowing in psychosis patients. Handwriting movements from 57 healthy participants and 70 psychosis patients were recorded on a digitizing tablet. Temporal and kinematic features were extracted from handwritten loops and circles. An independent objective measure based on peak velocity for circles written at maximum speed was used to classify patients as bradykinetic. Using a statistical cut-point derived from normative data, 64% of the patients met criterion for bradykinesia compared with 46% using a conventional observer-based severity rating scale. Bradykinetic patients produced handwriting movements with longer stroke durations, smaller amplitudes and lower peak velocities compared with non-bradykinetic patients. Thirty-six percent of the pen strokes produced by the bradykinetic patients were non-ballistic compare with 20% for the non-bradykinetic patients. The proportion of nonballistic movements observed in handwriting was unrelated to current antipsychotic dose, severity of negative psychosis or depression. The ease-of-use and standardization of a tablet-based approach to quantifying parkinsonian bradykinesia can aid in diagnosing parkinsonian bradykinesia in patients treated with antipsychotics.